State-of-the-Art Renewable Energy in Korea - Geem, Zong Woo; Hong, Junhee; Hwang, Woohyun (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nowadays, renewable energy plays an important role in our daily lives. This Special Issue addresses the current trend in the use of renewable energy in South Korea. The first aspect is a renewable-based power system, where both main and ancillary supplies are sourced from renewable energies; the second aspect is a distribution network for renewable energy; and the last aspect is a nanogrid network technology. Renewable energy requires many innovations over existing power infrastructure and regulation. These articles show the changing trend in various sectors in Korea.